Link & Learn - Wittenburg, Christine (Homœopathic Links, 2013)
This column is intended to stimulate discussion on the pages of LINKS and to share short formulated ideas and observations. Open is the keyword here: open to any subject; write with an open mind and an open heart; favour question marks over exclamation marks and be open to discussion. In a recent publication of a systematic review, homeopathy – besides not having benefits – is charged with causing harm. But “there is no evil without any positive outcome” (Spanish proverb), and the debate on adverse effects might illuminate the theme of primary effects, secondary effects and initial reactions of (not only!) homeopathic remedies. The work of M. Z. Teixeira – which makes adverse and rebound effects of conventional medicines available for homeopathy – will help me to disentangle this spiny subject.
Keywords: Adverse effects; Primary effects; Secondary effects; Rebound effects; Initial reactions; M. Z. Teixeira